2000
DOI: 10.1901/jeab.2000.74-101
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence Classes in Individuals With Minimal Verbal Repertoires

Abstract: Studies from two different laboratories tested for equivalence classes in individuals with severe mental retardation and minimal verbal repertoires. In the first study, 3 individuals learned several matching-to-sample performances: matching picture comparison stimuli to dictated-word sample stimuli (AB), matching those same pictures to printed letter samples (CB), and also matching the pictures to nonrepresentative forms (DB). On subsequent tests, all individuals immediately displayed Emergent Relations AC, AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
105
3
25

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 31 publications
6
105
3
25
Order By: Relevance
“…For example, we recently reported a study that demonstrated stimulus equivalence according to the criteria outlined by Sidman and Tailby (1982) in persons with minimal verbal ability (Carr, Wilkinson, Blackman, & Mcilvane, 2000). To our knowledge, no one has yet studied the potential of humans who lack verbal abilities and extensive discrimination training experience to form functional stimulus classes.…”
mentioning
confidence: 99%
“…For example, we recently reported a study that demonstrated stimulus equivalence according to the criteria outlined by Sidman and Tailby (1982) in persons with minimal verbal ability (Carr, Wilkinson, Blackman, & Mcilvane, 2000). To our knowledge, no one has yet studied the potential of humans who lack verbal abilities and extensive discrimination training experience to form functional stimulus classes.…”
mentioning
confidence: 99%
“…On the one hand, there are reports of equivalence emerging without naming (Carr, Wilkinson, Blackman, & McIlvane, 2000;Lazar, Davis-Lang, & Sanchez, 1984;Luciano, Gómez-Becerra, & Rodríguez-Valverde, 2007;O'Donnell & Saunders, 2003;Sidman & Tailby, 1982). And on the other hand, some authors have questioned those results, claiming that naming is necessary for equivalence to emerge (Carp & Petursdottir, 2015;Horne, Hughes, & Lowe, 2006;Horne, Lowe, & Randle, 2004;Lowe, Horne, Harris, & Randle, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Other research has assessed the linguistic conditions under which equivalence relations may emerge (De Alcântara Gil, de Oliveira, & McIlvane, 2011;Carr et al, 2000;Devany, Hayes, & Nelson, 1986;Peláez, Gewirtz, Sanchez, & Mahabir, 2000). One of those studies (Devany et al,1986) evaluated the relationship between the level of linguistic development and the establishment of equivalence relations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations